Metabolic Aging as an Increased Risk for Chronic Obstructive Pulmonary Disease - Claire J. Guo; Suneeta Godbole; Wassim W. Labaki; Katherine A. Pratte; Jeffrey L. Curtis; Robert Paine; Eric Hoffman; Meilan Han; Jill Ohar; Christopher Cooper; Katerina J. Kechris; Dawn L. DeMeo; et al. (Metabolites)
Background/Objectives: Both aging and chronic obstructive pulmonary disease (COPD) are strongly associated with changes in the metabolome; however, it is unknown whether there are common aging/COPD metabolomic signatures and if accelerated aging is associated with COPD. Methods: Plasma from 5704 subjects from the Genetic Epidemiology of COPD study (COPDGene) and 2449 subjects from Subpopulations and intermediate outcome measures in COPD study (SPIROMICS) were profiled using the Metabolon global metabolomics platform (1013 annotated metabolites). Post-bronchodilator spirometry measures of airflow obstruction (forced expiratory volume at one second (FEV1)/forced vital capacity (FVC) < 0.7) were used to define COPD. Elastic net regression was trained on never and former smokers with normal spirometry and no emphysema to create a metabolomic age score which was validated in SPIROMICS subjects. Results: Our metabolic age score was strongly associated with chronic age in the validation cohort (correlation coefficient = 0.8). COPD subjects with accelerated aging (>7 years difference between metabolic and actual age) had more severe disease compared with those who had decelerated aging (<−7 years difference between metabolic and actual age). COPD and aging metabolites were shared more than expected (p < 0.001), with amino acid and glutathione metabolism among pathways overrepresented. Conclusions: These findings suggest a common mechanism between aging and COPD and that COPD is associated with accelerated metabolic aging.